1999
DOI: 10.1128/jvi.73.2.1066-1074.1999
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Poliovirus with Its Receptor Affords a High Level of Infectivity to the Virion in Poliovirus Infections Mediated by the Fc Receptor

Abstract: Poliovirus infects susceptible cells through the poliovirus receptor (PVR), which functions to bind virus and to change its conformation. These two activities are thought to be necessary for efficient poliovirus infection. How binding and conformation conversion activities contribute to the establishment of poliovirus infection was investigated. Mouse L cells expressing mouse high-affinity Fcγ receptor molecules were established and used to study poliovirus infection mediated by mouse antipoliovirus monoclonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Poliovirus enters susceptible cells through a specific poliovirus receptor, but can also be taken up by FcγRs (Ref. 164), and FcγRs have been found to be expressed on both microglia and perivascular macrophages (Ref. 165).…”
Section: Fcγrs In Infectionmentioning
confidence: 99%
“…Poliovirus enters susceptible cells through a specific poliovirus receptor, but can also be taken up by FcγRs (Ref. 164), and FcγRs have been found to be expressed on both microglia and perivascular macrophages (Ref. 165).…”
Section: Fcγrs In Infectionmentioning
confidence: 99%
“…The cells were incubated at 37 uC for 8 h and then fixed with 3 % paraformaldehyde. The cells were stained by indirect immunofluorescence with rabbit hyperimmune serum against the PV 2C protein and Hoechst 33258 (Molecular Probes) for counterstaining (Arita et al, 1999). The numbers of infected cells were counted for the calculation of IU (Jackson et al, 2001).…”
Section: Construction Of An Expression Vector For Pv Capsid Proteinsmentioning
confidence: 99%
“…PVR-IgG2a is a chimeric molecule in which the extracellular moiety of human PVR is joined to the hinge and Fc region of a mouse IgG2a molecule (Arita, Horie, and Nomoto, 1999). Crude PVR-IgG2a was prepared from culture supernatants of recombinant baculovirus-infected Sf9 cells and purified on a protein A-Sepharose 4B column (Pharmacia Biotech) as described (Arita, Horie, and Nomoto, 1999). The concentration of PVR-IgG2a, considered as a dimer like an IgG, was determined by measuring the absorbance at 280 nm.…”
Section: Cells Viruses and Recombinant Pvrmentioning
confidence: 99%
“…Therefore, it is generally believed that the formation of 80S empty capsids results from viral uncoating. PVR-IgG2a (or CD155-IgG2a), a chimeric molecule consisting of an extracellular moiety of PVR and the hinge and Fc portion of a mouse IgG2a, together with Fc receptor-expressing cells, were used to confirm the importance of specific PV-PVR interactions in viral uncoating (Arita, Horie, and Nomoto, 1999). It has also been shown that PVR acts as a catalyst, increasing the rate of capsid transitions by lowering the activation barrier (Tsang et al, 2001).…”
Section: Introductionmentioning
confidence: 99%